Pelatihan CorelDRAW untuk Membuat Desain Logo di SMK Ibrahimy 1 Sukorejo Situbondo - Zaehol Fatah; Ach Yusril Ihza Mahendra (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Students at SMK Ibrahimy 1 Sukorejo Situbondo currently possess limited skills in logo design using the CorelDRAW application. This community service activity aimed to enhance participants' knowledge and skills in creating vector-based logo designs using CorelDRAW. The training was attended by 30 students and conducted through a combination of lectures, demonstrations, hands-on practice, discussions, and mentoring. Evaluation was carried out via observation during the activity, assessment of the logo designs produced, and the distribution of participant satisfaction questionnaires. The evaluation results indicated an average satisfaction rate of 90.6%, with the